Presidential approval in Costa Rica: Explaining typical and unusual patterns - Pignataro López, Adrián (2019)
We analyze presidential approval ratings in Costa Rica from 1980 to 2016, seeking to explain typical cycles of “honeymoon”, decay, and recovery, and the deviations that emerge from them: the two presidential terms of Oscar Arias. First, we show that party fragmentation has affected electoral support of the winning president and, as a consequence, his or her approval rate at the beginning of the mandate (i.e. the “honeymoon”). Using time series analysis, we then go on to model approval ratings as a function of economic and political variables. We find that social expenditure matters more than the macroeconomic indicators, and that the “Arias exceptionality” could be better understood as a result of higher social expenditure during his government and the coattails of the Nobel Peace Prize that he was awarded. Thus, social policy could be added to the theories of approval as a relevant variable in some contexts.